DOGMA ALLAH TRITUNGGAL DAN MASALAH DISTORSI AJARAN TRINITAS - Elfri Darlin Sinaga (Jurnal Theologia Forum STFT Surya Nusantara, 2019)
The teachings about the Trinity of God developed continuously from century to century. From recognition there is only One God, namely Jehovah and three divine persons (that is, in the days of the Old and NewTestaments), then developed from each century into various understandings. Although the council tried to integrate the idea of the Trinity, the problem could not be solved through the council. This happened not without the influence of the political rulers of the Roman empire in the first century to the fourth century. Then, it can be stated that there is a distortion that occurs about the Trinity or the Triune God. This study aims to find out the theological problems arisingfrom the distortion of the teachings of the Trinity by Roman authority.The method used is literature research, using a historical approach model. This research produces several ideas and understandings that are expected to contribute to the scientific world, especially in the distortion discourse of the teachings of the Trinity. The conclusions obtained from this literature study are as follows: (1) The Trinity in the pre-distortion era of teachings is the recognition of the existence of one God, Yahweh and acknowledging the plurality of the Divine person. (2) The teachings of the trinity develop from time to time due to the influence of the church (in this case bishops and church thinkers). Finally, the teachings of the trinity are more influenced by church traditions than by Bible reviews. (3) The Bible as the main source of teachings about God has been distorted by and on the authority of Rome. The distortion is carried out through councils (for political interests), amending Bible verses, and inculturation of pagan Roman beliefs with Christian beliefs. For this reason, the writer gives the following suggestions: (1) Care needs to be taken in translating the trinity and interpreting God, because the power of Rome in the first to fourth centuries has distorted the teachings of the trinity. (2) The trinity discourse needs to be carried out further research by subsequent researchers.